Functional soil property maps are just a click away - Okoth, Peter F. (International Center for Tropical Agriculture, 2011)
With data provided by the Africa Soil Information Service (AfSIS), farmers, agricultural experts, and natural resource managers will be able to identify the best options for sustainably improving crop production and better managing the land, including contributing to better ecosystem services management at regional, national, and local levels. The AfSIS project involves probing the landscape of sub-Saharan Africa, using a variety of highly accurate digital soil mapping techniques including remote sensing, infrared and x-ray spectroscopy scanning techniques, to create detailed soil maps. The data generated will also allow climatic change prediction with soil as a major input into the modeling. Launched in January 2009, and using 60 randomly selected 10 x 10 km sampling locations to characterize the soils, the AfSIS project has completed 25 of the 60 projected sampling locations making the objective of completing the remaining 35 locations feasible by October 2012. Countries so far sampled include Tanzania, Ethiopia, Malawi, Mozambique, South Africa, Ghana, Mali, and Nigeria. The information generated so far is now freely available from AfSIS website: www.africasoils.